Comparative assessment of patient satisfaction with medical care before and after the implementation of the Public-Private Partnership (PPP) project, taking into account health literacy. - Maira, Alimbetova; Danyshbayeva, Aizhan (Bangladesh Journal of Medical Science, 2025)
Background There is conflicting scientific evidence on the impact of the PPP model on patient satisfaction with medical care. The accumulated experience according to research data is currently insufficient to draw any unambiguous conclusions. The purpose of this study was to compare patient satisfaction with the medical care provided before and after the implementation of the PPP project, taking into account medical literacy. Materials and methods A cross-sectional study was conducted with the participation of 217 people treated in the hospital of the Almaty Multidisciplinary Clinical Hospital three years before the implementation of the PPP project from 2017 to September 2020 and 241 patients three years after the implementation, from September 2020 to January 2024. Patients of both groups were assessed for satisfaction with the quality of medical care provided, using an adapted HEALTHQUAL – Kz questionnaire and an assessment of medical literacy using a version of the European HLS19 questionnaire adapted for the Russian— speaking population (HLS19 - Q22-RU). The level of statistical significance was determined as p<0.05. The statistical analysis was performed in the SPSS-statistical 26.0 program. Results In general, the implementation of the PPP project has had a positive impact on patient satisfaction with the medical services provided. Patients were more satisfied with the hospital infrastructure before PPP 2.91 (±0.85), after – 4.11 (±0.82), (p<0.001), the efficiency of the medical staff, which amounted to 3.03( ±093) before the introduction of PPP, after – 4.10 (±0.74), (p<0.001), and the results of the services rendered, up to -3.16 ±(1.01), after – 4.22 (±0.75), (p<0.001). Conclusion The implementation of the PPP project in the AMKB contributed to improving patient satisfaction with the medical services provided. It is also necessary to determine the level of medical literacy before assessing satisfaction with the quality of medical care, if sufficient and excellent, you can treat the results as more objective and critically evaluated. BJMS, Vol. 24 No. 03 July’25 Page : 950-956